2018
DOI: 10.20448/journal.510.2018.51.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of L-Asparaginase Produced from Vigna Unguiculata

Abstract: The present study aimed to production of purified L-asparaginase from Vignaunguiculata. Different physiological parameters, such as pH, temperature and incubation period, were optimized for growth and maximum L-asparaginase production. The optimum parameters were 37°C, 30 min and pH 8.5. Maximum L-asparaginase was 886.4U/ml with a specific activity of 1140.7 U/ml (31 fold purification with 28 %yield) were obtained at optimum conditions. The purified L-asparaginase produced from Vignaunguiculata was used for ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 45 publications
2
25
0
2
Order By: Relevance
“…After 30 min the activity of enzymedepleted. The findings are in close comparison with Moharib (2018) who revealed 30 min optimal reaction time for L-asparaginase extracted from Vigna unguiculata seed.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…After 30 min the activity of enzymedepleted. The findings are in close comparison with Moharib (2018) who revealed 30 min optimal reaction time for L-asparaginase extracted from Vigna unguiculata seed.…”
Section: Discussionsupporting
confidence: 82%
“…While the substrate optimal concentration determined from Capascium annum L was 33mM, where catechol was acting as substrate in the mixture (Arnnok et al, 2010). While Moharib (2018) has revealed 200mMoL concentrationof substrate for maximal activity of L asparaginase activity derived from Vigna unguiculata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6. Effect of some metal ions and EDTA on L-asparaginase activity produced by A. terreus (2018) 48 who reported that cytotoxic activity of L-asparaginase was tested on HELLA, MCF7, HEPG2 and HCT-116 showing that L-aspargenase had higher growth inhibition against Hep-G2 and HCT-116 than Hella and MCF7 carcinoma cell lines. El-Naggar et al (2016) 42 studied the activity of L-asparaginase against CACO 2, HeP 2, HePG 2 cancer cells and reported that IC 50 was 2 -4 U/ml with the highest activity against CACO 2.…”
Section: Cytotoxicity and Anticancer Activities Of The Purified L-aspmentioning
confidence: 99%
“…L-ASP induces cytotoxicity by breaking asparagine into L-aspartate and ammonia. According to Moharib, the cytotoxic activity of L-ASP is closely related to asparagine, and the asparagine level differed among various cell lines [30]. erefore, L-ASP induced cancer cell death to varying degrees.…”
Section: Cytotoxicity Activitiesmentioning
confidence: 99%